Factors Influencing Time-Dependent Quality Indicators for Patients With Suspected Acute Coronary Syndrome. Issue 1 (March 2020) - France, Daniel J.; Levin, Scott; Ding, Ru; Hemphill, Robin; Han, Jin; Russ, Stephan; Aronsky, Dominik; Weinger, Matt
Abstract : Objectives: Rapid risk stratification and timely treatment are critical to favorable outcomes for patients with acute coronary syndrome (ACS). Our objective was to identify patient and system factors that influence time-dependent quality indicators (QIs) for patients with unstable angina/non–ST elevation myocardial infarction (NSTEMI) in the emergency department (ED). Methods: A retrospective, cohort study was conducted during a 42-month period of all patients 24 years or older suspected of having ACS as defined by receiving an electrocardiogram and at least 1 cardiac biomarker test. Cox regression was used to model the effects of patient characteristics, ancillary service use, staffing provisions, equipment availability, and ED and hospital crowding on ACS QIs. Results: Emergency department adherence rates to national standards for electrocardiogram readout time and biomarker turnaround time were 42% and 37%, respectively. Cox regression models revealed that chief complaints without chest pain and the timing of stress testing and medication administration were associated with the most significant delays. Conclusions: Patient and system factors both significantly influenced QI times in this cohort with unstable angina/NSTEMI. These results illustrate both the complexity of diagnosing patients with NSTEMI and the competing effects of clinical and system factors on patient flow through the ED.